Analisis Tingkat Suku Bunga Bank, Subsidi BBM dan Harga Minyak Dunia Terhadap Inflasi di Indonesia - Aditya, Muhammad Bagus; Sopiana, Yunita (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This study aims to analyze the effect of bank interest rates, fuel subsidies and world oil prices on inflation in Indonesia for the 2006-2021 period. The scope of this study focuses on the variables to be studied, namely bank interest rates, fuel subsidies, world oil prices and inflation. in Indonesia with a research period of 2006-2021. Annual data in the form of quantitative data is used in this study. The research method used is Ordinary Least Square (OLS). The Eviews program serves as the software used in this study. The results of this research analysis show that bank interest rates and world oil prices have a positive and significant effect on inflation, and fuel subsidies have a negative and insignificant effect on inflation.